Temporary Storage of the Human Nasal Tissue and Cell Sheet for Wound Repair - Kasai, Yoshiyuki; Morino, Tsunetaro; Dobashi, Izumi; Mori, Eri; Yamamoto, Kazuhisa; Kojima, Hiromi (Frontiers in Bioengineering and Biotechnology, 2021)
Temporary storage of nasal tissues and nasal cell sheets is an important issue for regenerative medicine which including transportation between hospital and cell culture facility. Herein, we investigated chilled and frozen preservation of nasal tissues and expiry dates of nasal cell sheets in a ready-to-use condition. In preserved tissue, although the cell number was lower than that in fresh tissue, nasal cell sheets could be fabricated from tissues that had been refrigerated for 5 days and frozen-thawed over 5 days. Moreover, the nasal mucosal cell sheets were preserved in non-hazardous buffer. The cell number, viability, and structure were not maintained in saline containing E-cadherin for 2 days; these factors were maintained in Hank’s balanced salt saline for 2 days but not for 5 days. To address the proliferation capacity cells on the stored cell sheets, we performed cell sheet grafting assays in vitro. Cell sheets stored in Hank’s balanced salt saline for 2 days adhered to collagen gel and expanded normally. Therefore, the nasal tissues can be stored temporarily in refrigerators or deep freezers, and Hank’s balanced salt saline can be used as a ready-to-use preservative solution for cell sheets for a few days.